Evaluating the performance of a new ergonomic laparoscopic needle holder for intracorporeal suturing - Arturo Minor-Martínez; Ricardo Manuel Ordorica-Flores; Juan Ramón Mota-Carmona; Iván Tlacaélel Franco-González; Jesús Tapia Jurado; Fernando Pérez-Escamirosa (PLoS ONE, 2025)
In laparoscopy, the absence of ergonomics in the instruments affects the performance and efficiency of the surgeon, increasing the likelihood of developing musculoskeletal injuries. This article presents the development of a laparoscopic needle holder with an ergonomic handle and the experience in its use with surgeons in the intracorporeal suturing task. The handle of the laparoscopic needle holder consists of a semi-spherical piece that easily adapts to the palm of the surgeon’s hand and improves the posture and ergonomics of the wrist, allowing the direct transmission of rotational movements around the longitudinal axis of the instrument towards the tip. Moreover, a spring-loaded mechanism allows the tip of the tool to be opened and closed in a normally closed configuration, with enough pressure to hold different surgical needles. Twenty-two pediatric surgery surgeons and residents, without upper extremity musculoskeletal disorders, participated in this study. Each participant performed the intracorporeal suturing task using two laparoscopic needle holders (conventional and with ergonomic handle) in a laparoscopic simulator. Motion data from both instruments were captured and the performance was assessed by means of 16 motion analysis parameters (MAPs). The performance of the residents improved markedly using the laparoscopic needle holder with ergonomic handle, obtaining statistically significant differences in 10 MAPs evaluated. The comparison of the results of each instrument showed that this ergonomic laparoscopic needle holder stood out over the conventional tool, improving psychomotor skills and the ability to control the angular position and rotational movements of the instrument on its own axis, indispensable for intracorporeal suturing. The innovative design of the laparoscopic needle holder with ergonomic handle allows for better transfer of rotational movements from the surgeon’s hand directly with the longitudinal axis to the tip, reducing extreme wrist positions and excessive effort to open and close the tip of the instrument during intracorporeal suturing.